Correlation between periodontal disease indices and lung cancer in Greek adults: a case — control study - Chrysanthakopoulos, N.A. (Experimental Oncology, 2016)
Aim: The aim of the present case — control study was to examine the possible associations between periodontal disease indices and the risk of lung cancer development in a sample of Greek out-patients referred to a medical and a dental private practice. Materials and Methods: A total of 200 individuals were interviewed and underwent an oral clinical examination, and 64 of them were suffered from several histological types of lung cancer. The estimation of the possible associations between lung cancer as a dependent variable and periodontal disease indices as independent ones was carried out by using a multiple regression analysis model. Results: Probing pocket depth (odds ratio (OR) = 2.72, 95% confidence interval (CI) 1.05–7.06), clinical attachment loss (OR = 3.51, 95% CI 1.30–9.47) bleeding on probing (OR = 1.93, 95% CI 0.98–3.81) were significantly associated with the risk of developing lung cancer. Smoking (OR = 2.49, 95% CI 1.20–5.17) was significantly associated with the mentioned risk, whereas it was consisted as a confounder regarding the estimated associations between moderate/severe clinical attachment loss and presence of bleeding on probing with the risk of developing lung cancer. Conclusion: Probing pocket depth as an index for periodontal disease severity was statistically significantly associated with the risk of developing lung cancer.